Analysis on the voltage stability on transmission network with PV interconnection - Karmila Kamil; Muhammad Amirul Ashraf Ab Rahman; Chong Kok Hen; Halimatun Hashim; Mohd Helmi Mansor (Institute of Advanced Engineering and Science, 2019)
Voltage stability means the ability of the power system network to maintain steady-state voltage value at all buses in the system under normal condition and after being subjected to a disturbance. This research highlights the effect of solar photovoltaic (PV) as the subject of disturbance to the network system as this kind of energy source has emerged towards higher level of integration into the national grid. High penetration of solar PV into the grid may cause several issues of stability and security to the system particularly effecting the normal voltage and line overloading. This research is focused on the simulation of power flow to study the transmission network behavior with and without the solar PV interconnection. To accomplish the research objectives, the network system will be modelled in a software known as Power System Simulator for Engineering (PSSE). The simulation result will be discussed and analyzed using Voltage Stability Indices (VSI) to prove and strengthen the theory behind the literature review.